SIFAT FISIK DAN WAKTU BAKAR BIOBRIKET LIMBAH PELEPAH KELAPA SAWIT - Muhammad Fajri Noor; Muhammad Faisal Mahdie; Diana Ulfah (Jurnal Sylva Scienteae, 2022)
. Indonesia government targets the use of new and renewable energy mix of 23% by 2025 as stated in RUEN. Indonesia is ranked 1st in the world's palm oil producer with 47,120,247 tons and 1st in the world's palm oil area with an area of 14,456,611 ha. One hectare of oil palm plantations in South Kalimantan has the potential to produce 4.4 million tons in one year. The dry frond waste from the pruning of oil palm can be used for processing biobriquettes. This study purpose to obtain the moisture content, ash content, volatile matter, calorific value, and burning time of the biobriquettes of oil palm fronds produced based on particle size. The results of the biobriquette waste from oil palm fronds in this study contained a moisture content of 7.20% - 12.60%, ash content of 3.60% - 8.54%, volatile matter 34.85% - 55.12%, a value of 34.85% - 55.12%. the heat is 3,020 cal/g – 5,091 cal/g, the burning time for smoldering is 61 minutes – 74 minutes, and the burning time for boiling 500ml water is 18 minutes – 25 minutes. The results showed that the particle size affects the quality standards of briquettes and burning time. The lower the moisture content and ash content, higher the calorific value so fast that the boiling water is 500 ml. The best results were found in treatment C with a particle size 80 mesh with an average the calori value of 4.952 cal/g.Pemerintah Indonesia mempunyai target pada tahun 2025 yaitu penggunaan bauran etb sebesar 23% yang tertuang pada RUEN. Indonesia mendapatkan peringkat 1 Produsen Kelapa Sawit Dunia dengan 47.120.247 ton; peringkat 1 Luas Areal Kelapa Sawit Dunia dengan luas 14.456.611 ha. Perkebunan kelapa sawit di Kalimantan Selatan berpotensi menghasilkan 4,4 juta ton/hektar/tahun. Limbah pelepah kering hasil pemangkasan kelapa sawit dapat dipergunakan untuk pengolahan biobriket. Penelitian ini bertujuan untuk mendapatkan besarnya nilai kadar air, kadar abu, kadar zat terbang, nilai kalor, dan waktu bakar dari biobrlket limbah pelepah kelapa sawit yang dihasilkan berdasarkan ukuran partikel. Hasil biobriket limbah pelepah kelapa sawit dalam penelitian ini mengandung kadar air sebesar 7,20% - 12,60%, kadar abu sebesar 3,60% - 8,54%,  zat terbang sebesar 34,85% - 55,12%, nilai kalor sebesar 3.020 kal/g – 5.091 kal/g, waktu bakar dari lamanya membara selama 61 menit – 74 menit, dan waktu bakar dari pendidihan 500ml air selama 18 menit – 25 menit. Hasil penelitian menunjukan bahwa ukuran partikel mempengaruhi standar kualitas briket dan waktu bakar. Semakin rendah kadar air dan kadar abu maka nilai kalor semakin tinggi sehingga mempercepat pendidihan 500ml air. Hasil yang terbaik yaitu terdapat pada perlakuan C yaitu dengan ukuran partikel 80 mesh dengan rata rata nilai kalor 4.952 kal/g